Ethnomathematical exploration of the Remo dance as a source for mathematics learning - Eka Sulistyawati; Brenda Indah Nirmala; Dewi Hamidah (Jurnal Elemen, 2025)
Mathematics and dance are connected to both content and processes. This research aimed to explore Remo dance elements of movement, fashion accessories, and accompanying musical equipment as sources of mathematics learning. This ethnographic study was conducted at one of the oldest dance studios in the Kediri district. The research subjects were three Remo dance experts, consisting of a studio owner and two professional Remo dancers. Data were collected by interviewing the sources and observing and documenting dances. The data analysis uses triangulation based on the results of observations, documentation, and interviews. The exploration of mathematical concepts found in Remo dance was then analyzed using interrater reliability based on the agreement of three mathematics education experts. The results revealed 17 mathematical concepts in the Remo dance exploration of movement elements, fashion accessories, and accompanying musical equipment with almost perfect reliability categories. As a mathematics learning source, the Remo dance context can be applied to learning activities, preparing materials, and preparing test instruments.